More insecure and less paid? The effect of perceived job insecurity on wage distribution - Sergio Scicchitano; Marco Biagetti; Antonio Chirumbolo (Global Labor Organization (GLO), 2018)
This article employs a Counterfactual Decomposition Analysis (CDA) using both a semi-parametric and a non-parametric method to examine the pay gap, over the entire wage distribution, between secure and insecure workers on the basis of perceived job insecurity. Using the 2015 INAPP Survey on Quality of Work, our results exhibit a mirror J-shaped pattern in the pay gap, with a significant sticky floor effect, i.e. the job insecurity more relevant at the lowest quantiles. This pattern is mainly due to the characteristics effect, while the relative incidence of the coefficient component accounts roughly for 22 up to 36% of the total difference, being more relevant at the bottom of the wage distribution.
Keywords: J31; J82; C14; 330; Job (in)security; Counterfactual distribution; Semi-parametric methodology; Nonparametric methodology; Wage gap; Blinder/Oaxaca; Quantile regression; Italy